Markets and Manipulation : Time for a Paradigm Shift? - Basu, Kaushik (World Bank, Washington, DC, 2016)
There is a growing appreciation in economics that people have emotional vulnerabilities, commitments to social norms, and systematic irrationalities, which impact their decision making and choice in the marketplace. The flip side of this is that human beings are susceptible to being manipulated by unscrupulous agents who are single-minded about marketing their services and wares. This paper reviews George Akerlof and Robert Shiller's book, Phishing for Phools: The Economics of Manipulation and Deception, alongside other writings in the field, and discusses how this research agenda can be taken forward. The paper shows how this new research can shed light on the ubiquity of corruption in so many societies, and proposes ideas for controlling corruption.